2008
DOI: 10.5253/078.096.0110
|View full text |Cite
|
Sign up to set email alerts
|

Biometrics, Sexual Dimorphism and Gender Determination of Griffon VulturesGyps fulvusfrom Crete

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…The analyses for juveniles and non-juveniles were conducted separately, following similar studies of sex determination (e.g., Delgado andPenteriani 2004, Xirouchakis andPoulakakis 2008), by means of a two-step procedure as follows. First, normality tests were run for all variables by means of Kolmogorov-Smirnov (K-S) and Shapiro-Wilk's tests (Zar 1996).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses for juveniles and non-juveniles were conducted separately, following similar studies of sex determination (e.g., Delgado andPenteriani 2004, Xirouchakis andPoulakakis 2008), by means of a two-step procedure as follows. First, normality tests were run for all variables by means of Kolmogorov-Smirnov (K-S) and Shapiro-Wilk's tests (Zar 1996).…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly the case of vultures, which lack obvious external morphometric differences. Although several studies have used external morphometrics for sex determination in some species of raptors (Ferrer and De Le Court 1992, Balbontín et al 2001, Palma et al 2001, Martínez et al 2002, Delgado and Penteriani 2004, Zuberogoitia et al 2005, 2011, including some vulture species (De la Puente and Elorriaga 2004, Xirouchakis and Poulakakis 2008), there is a dearth of data for many species of conservation concern, such as the en-1 Email address: Pascual.Lopez@uv.es dangered Bearded Vulture (Gypaetus barbatus). For this species, sex determination by molecular methods has been recently optimized (García et al 2009).…”
mentioning
confidence: 99%
“…This result is similar to those obtained by Ito et al [3] who reported unsuccessful sex identification in 6 species of Accipitridae because of differences between 2-8 bp of fragments from CHD-W and CHD-Z. In contrast, Xirouchakis and Poulakakis reported sex identification of individuals of Eurasian griffon vulture using P2-P8 primers, CHD segments with differences of 9 bp that could be differentiated using polyacrylamide gels; although, could not be applied in this case with Golden eagle, the resulting 8% polyacrylamide gels also displayed a virtual single band, like in the agarose gels (data not shown) [13].…”
Section: Discussionmentioning
confidence: 80%
“…The gene coding for Chromobox-Helicase-DNA binding protein (CHD) was the first W chromosome described, and enabled sex identification in most avian species using a simple method consisting on the amplification of CHD genes of both sex chromosomes (CHD-W, CHD-Z) whose lengths are different because of varying size of introns [11], using a couple of primers P2 and P8 [12]. It has been reported that this technique is not applicable to Accipitridae birds such as eagles, although Xirouchakis and Poulakakis reported the sex identification of 49 individuals of Eurasian griffon vulture (Gyps fulvus) using P2-P8 primers [13]. In order to have a reliable method for sex identification in Accipitriformes modifications to the technique have been developed using the Amplification Refractory Mutation System "ARMS" [3,9,14] ARMS is a PCR-based technique to amplify specific alleles using a 3'-terminal primer (MP) that fits to one allele variant and mismatches to the other (P2, NP) allowing the detection of allele differences between CHD-W and CHD-Z genes [3].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of age and sex are important in population studies as they inform the research of population dynamics (Hughes 1998). Both sexes of the Cape Vulture are alike in plumage (Mundy et al 1992) and like all vultures of the genus Gyps, they appear to lack plumage characteristics or external features to distinguish between sexes (Xirouchakis & Poulakakis 2008). This makes it very important to develop sexing techniques that can be applied in the field.…”
Section: Introductionmentioning
confidence: 99%